Resting cardiac function in adolescent non-suicidal self-injury: The impact of borderline personality disorder symptoms and psychosocial functioning. (February 2017) - Koenig, Julian; Rinnewitz, Lena; Parzer, Peter; Resch, Franz; Thayer, Julian F.; Kaess, Michael
Abstract: Vagally mediated heart rate variability (vmHRV) is reduced in borderline personality disorder (BPD). Non-suicidal self-injury (NSSI) is associated with comorbid psychopathology, in particular BPD. We aimed to examine differences in cardiac function (vmHRV and heart rate [HR]) comparing adolescents (12–17 years) engaging in NSSI (n=30) and healthy controls (n=30). Further, we aimed to determine clinical concomitants of cardiac function in patients with NSSI. Analyses showed no significant group differences on cardiac function. Controlling for a host of confounding variables resting state HR and vmHRV in adolescents with NSSI were significantly correlated with BPD symptoms and the current level of functioning. Highlights: Cardiac function is not altered in adolescent non-suicidal self-injury (NSSI). Cardiac function is related to BPD symptoms and the current level of functioning. Future studies should address cardiac function in the longitudinal course of NSSI.